A telemedicine tool for acute stroke management in Malaysia: a smartphone application - Hong Chuan Loh; Teck Long King; Irene Looi; Wan Chung Law (BMC Neurology)
Abstract Background Accurate assessment of stroke severity, precise neuroimaging diagnosis, and seamless coordination among stakeholders are crucial in ensuring prompt diagnosis and treatment during acute stroke activation. The study aimed to assess how the telestroke tool JOIN enhances time metrics in acute stroke care, specifically by improving decision-making speed and thereby enhancing patients’ clinical outcomes. Methods This prospective cohort study was conducted at Seberang Jaya Hospital and Umum Sarawak Hospital in Malaysia. It included adult ischaemic stroke patients who arrived within 4.5 h of stroke onset at one of the two locations. Patients were divided into two groups: the pre-JOIN period using conventional communication versus the JOIN period using JOIN. Time metrics were collected from medical records and/or social networking services (pre-JOIN), and timestamp data (JOIN). Analysis was performed using the Statistical Package for the Social Sciences, with a total sample size of 120 patients. Results With 60 patients in each group (pre-JOIN and JOIN), the mean (SD) ages were 57 (12.6) and 60 (14.1) respectively. Patients in both groups were similar at baseline, showing comparable stroke subtypes, events, and severity, primarily Lacunar Anterior Circulation Infarct with mild stroke as their initial occurrence. Both median door-to-imaging time and door-to-decision time were reduced by 6 min with JOIN, although the difference was not statistically significant. Thrombolysis rates and symptomatic intracranial haemorrhages were similar between groups, but door-to-needle time was significantly shorter with JOIN (78 [28.0] minutes versus 45 [42.0] minutes, p = 0.008). Most patients were discharged alive with similar modified Rankin Scale scores between the groups. Conclusions Door-to-needle time was shorter in the post-JOIN period than in the pre-JOIN period, suggesting that the implementation of JOIN may contribute to improved time metrics in acute stroke care. Its safety, affordability, ease of use, and additional features make it a promising telestroke tool, crucial for handling high patient volumes with limited resources. Trial registration This study was registered with the Malaysian National Medical Research Register and received ethical approval (NMRR ID-21-02363-XFT) from the Medical Research and Ethics Committee, Ministry of Health Malaysia dated 30-March-2023.